Partículas de prueba con espín en experimentos tipo Michelson y Morley (2018)
Abstract: In this thesis, we characterize, with help of the numerical relativity, the gravitomagnetic effects for spinning test particles when are moving in a rotating field. Since this aim, we numerically solve the Mathisson-Papapetrou-Dixon equations in a Kerr metric. Also, we study the ináuence of value and orientation of the spin in the clock effect.